Alert Learning School for the Elderly - Velasco, Julius M.; Roxas, Joel A. (Diliman, Quezon City College of Engineering, 2005)
This study is about the feasibility of establishing a special school for the elderly in Metro Manila, called Alert Learning School for the Elderly. The feasibility study was composed of the following phases: Market Study, Technical Study, Organization and Management Study, Financial Study, and the Social Profitability Study. The target market was defined in the Market Study. They are the senior citizens of Metro Manila aging 60-69 years old. Moreover, the number of enrollees and the sales revenues for the next five years (from 2006-2010) were projected. An initial demand of 758 students which translates to Php 4,169,000 for the first year of operation in 2006 was forecasted. Plans for marketing and promotions were also studied. A total of Php 136,750 was budgeted for the Marketing Strategy for the first year, decreased to Php 58,000 for the following years of operations. In the Technical Study, the curriculum of education of the five-year plan was laid down. The necessary school facilities and equipment were studied and planned. The location (Nuebe de Pebrero, Mandaluyong City) and the layout of the school building were also planned feasibly. The feasible type of ownership was determined to be a corporation, consisting of the general manager, and all other school personnel. In the Financial Study, the rate of return was determined to be 45%, while the payback period was pegged at 1.58 periods which in this case is 1.58 years or one (1) year and seven (7) months, both values being extremely acceptable. The net present value was determined to be Php 3,987,875.00 and the internal rate of return was 51.94. The Social Profitability study shows that aside from benefiting the Alert Learning School for the Elderly and the end-users, the project also has a significant impact in the community. This includes the generation of jobs, the patronization of local suppliers, and the implementation of quality education for the senior citizens of Metro Manila. In addition to these, the municipal tax, corporate income tax, and personal income tax which result from the project will also help both the local government and the national government. Furthermore, qualitative benefit like providing a social welfare for the adult senior citizens is also considered beneficial. A benefit-cost ratio of 1.53 goes to show that the benefits outweigh the costs. In general, an overall conclusion can be made that establishing the Alert Learning School for the Elderly is a feasible venture idea.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Alert Learning School for the Elderly; Adult education; Participatory monitoring and evaluation (Project management)